MASS MEDIA MONOPOLY IN INDONESIA IN THE MEDIA BUSINESS INDUSTRY - Putra, Dwi Kurniawan Riyadi; Cahyati, Witri; Gissani, Muhammad Fikri (PT Altin Riset Publishing, 2025)
This study aims to critically examine the phenomenon of media monopolies in Indonesia and their implications for press freedom, content diversity, and democratic discourse. Mass media play a crucial role in society as a provider of information, education, entertainment, and social control, as stipulated in Law No. 40 of 1999 on the Press. However, the persistence of monopolistic practices, despite the prohibition outlined in Law No. 5 of 1999 on Monopolistic Practices and Unfair Business Competition, raises significant concerns regarding the imbalance between regulation and reality. Employing a qualitative research design with a literature study approach, this research synthesizes scholarly journals, books, and legal documents to interpret the patterns and consequences of media concentration in Indonesia. The methodology allows for the integration of diverse perspectives from communication studies, economics, law, and political science, thereby constructing a comprehensive understanding of media monopoly dynamics. The findings reveal that media ownership in Indonesia is highly concentrated among a few conglomerates, leading to reduced content diversity, weakened independent journalism, and narrowed public discourse. Digital transformation, while initially viewed as a democratizing force, has enabled new configurations of monopoly, with algorithms and platform dominance amplifying established corporate voices and marginalizing smaller players. Regulatory gaps and limited enforcement capacity further exacerbate these issues, allowing oligopolistic practices to persist across traditional and digital domains. This study concludes that addressing media monopolies requires robust regulatory reforms, strengthened institutional frameworks, and enhanced media literacy initiatives to preserve pluralism, ensure press freedom, and maintain the democratic function of the media.